Gestión del conocimiento y su relación con el desempeño laboral en el Gobierno Regional de Loreto, 2019 - Rodríguez Chavez, Javier (2021)
This research entitled: Knowledge management and its relationship with job performance in the Regional Government of Loreto, year 2019; which has been a descriptive-correlational study and non-experimental design, whose study population was made up of 68 workers, who were surveyed through a questionnaire as a data collection instrument, concluding that it was determined that the knowledge management developed in the institution is deficient, because managers have difficulties in evaluating the knowledge and skills of the staff, which allow them to know the weaknesses that must be reinforced, also give little importance to the development of training or courses that allow Improve the performance of your actions. On the other hand, it was possible to determine that the labor performance of the GORE Loreto workers is low, since a large part of them show a lack of interest in carrying out their work with quality, and they are not very communicative, which makes their teamwork difficult, and you see the commitment that must be made towards the institution, it has also been identified that many of the workers have behavioral problems, demonstrated in the lack of kindness and courtesy in the interaction with users, managers and colleagues. Finally, it is determined that, knowledge management is significantly related to work performance in the Regional Government of Loreto, in 2019, being corroborated by the correlation coefficient –Rho de Spearman– of 0.820 which being a Index close to 1 shows that there is a positive and high relationship.